ANALYSIS OF ANTIMICROBIAL SUSCEPTIBILITY PATTERN OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS IN A TERTIARY CARE HOSPITAL - REPATI GOWRI; S A RAHIL PASHA; PARIMALA S; ARVIND NATARAJAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The present study aimed to evaluate MRSA prevalence among Staphylococcus aureus isolates, identify demographic factors associated with infections, and evaluate susceptibility to various antibiotics. Material and Methods: The study involved various clinically infectious samples. S. aureus was identified using a battery of tests and MRSA was identified utilizing the cefoxitin disk diffusion technique. At the same time, adherence to Clinical and Laboratory Standards Institute protocols guided the execution of the antibiotic susceptibility assay. Results: Out of 28,239 culture samples, 569 S. aureus isolates were detected, with 308 (54.1%) being MRSA. Most samples originated from individuals aged 41–60 years (n=110, 36%), and males accounted for (n=205, 67%) of the isolates. Pus samples notably yielded the highest proportion of MRSA (n=249, 80.8%), primarily from the surgery ward (n=120, 38.9%). Remarkably, the strains demonstrated substantial sensitivity (>90%) to linezolid, vancomycin, chloramphenicol, and doxycycline. Conclusion: In summary, MRSA strains were sensitive to drugs such as linezolid, vancomycin, chloramphenicol, and doxycycline. The emergence of resistant variants emphasizes the necessity for continuous surveillance and careful antibiotic use, informing antibiotic stewardship programs and clinical strategies for managing MRSA infections in health-care settings.